Manajemen Perubahan Organisasi dan Kesiapan Perilaku Karyawan dalam Implementasi E-Business di Era Digital: Sebuah Tinjauan Literatur - Wildana, Novan; Rahmadan, Rizki; Surman (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Digital transformation drives organizations to adopt e-business systems to improve operational efficiency. However, rapid technological developments are not always accompanied by the digital readiness of human resources (HR), especially in developing countries like Indonesia, which can trigger techno-anxiety in employees. This study aims to analyze the triggers of techno-anxiety and evaluate change management strategies in e-business implementation. The study used a literature review method with a qualitative-descriptive approach. Articles were obtained through a scientific database search using keywords such as techno-anxiety, technostress, digital transformation, e-business, and change management. Selected articles were scientific articles published between 2018 and 2026 that were relevant to the research focus and available in full text. Articles that were irrelevant or did not address techno-anxiety and employee readiness were excluded. A total of 13 articles were analyzed through theme grouping, comparison of findings, and narrative synthesis. The synthesis identified three main themes: concerns about system errors, data security, and limitations of adaptive training. The findings suggest that overly top-down change management has the potential to increase employee resistance and frustration. Therefore, change strategies need to be human-oriented through participatory engagement, adaptive training, open communication, and a psychologically safe work environment to reduce techno-anxiety and technostress.